Editorial - Cock, I.E. (Pharmacognosy Communications)
Dear readers and authors, I am pleased to bring you volume 6, issue 3 of Pharmacognosy Communications. In my previous editorial, I high- lighted some format changes which the journal has recently implemented, aimed at improve the presentation of each manuscript and increasing the publications exposure. In particular, Pharmacognosy Communications now includes ‘Graphical Abstracts’ which allow authors to provide potential readers with a quick understanding of the importance and relevance of the study. We now also include a concise ‘Research Highlights’ section with each manuscript. This is a short section containing 4-6 dot points that summarise the core findings of the study. We are also giving authors the opportunity to include author profiles, with or without accompanying photographs of the authors. I request that authors consider these changes and develop quality, visually appealing sections to help highlight their valuable work and to make it more readily accessible. It is through innovations such as these that we aim to increase the exposure and citation of Pharmacognosy Communications publications, and thus to build a credible impact factor for the journal.